Towards development of fibre-optic surface enhanced Raman spectroscopy probes using 2-photon polymerisation for rapid detection of bacteria - Kim,JA; Wales,DJ; Thompson,AJ; Yang,G-Z (SPIE, 2019)
In this study, a variety of direct laser written surface-enhanced Raman spectroscopy (SERS) micro-structures, designed for bacteria detection, are presented. Various SERS micro-structures were designed to achieve both a high density of plasmonic hot spots and a strong probability of interaction between the hot spots and the target bacterial cells. Twophoton polymerization was used for initial fabrication of the polymeric skeletons of the SERS micro-structures, which were then coated with a 50 nm-thick gold layer via e-beam evaporation. The micro-structures were fabricated on glass coverslips and were assessed using a confocal Raman microscope. To this end, Rhodamine 6G was used as an analyte under 785 nm laser illumination. The optimal SERS micro-structures showed approximately 7×103 enhancement in Raman signal (analytical enhancement factor, AEF) at a wavenumber of 600 cm-1. Real-time detection of E. coli in solution was demonstrated using the fabricated SERS platform with low laser powers and a short acquisition time (785 nm, 5 mW, 50 ms).